IMPLEMENTATION OF A TECHNOLOGICAL ORIENTED APPROACH IN THE SYSTEM OF PROFESSIONAL TRAINING OF ENGINEERS IN TECHNICAL UNIVERSITY - Кокарєва, А. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
Technologically oriented approach involves focusing the teaching staff on the student - his motives, goals, structure of educational activity, result. It is obligatory to achieve the goal of training in the structure of quality work of the teacher, which is possible provided that the interests of the student, his level of knowledge and skills, orientation of the educational process in accordance with the development of personality. That is, the existing level of students’ capabilities and knowledge is initially reflected, at which a new level of growth is being built. Moreover, the implementation of methodical means (organization and techniques, methods, forms, means of studying the educational material) is carried out taking into account the abilities, motives, needs, as well as stimulation of personal intellectual activity without unnecessary fixing of mistakes, failures, development of the student’s personality, his cognitive processes, activities. . The teacher has to define the nomenclature of educational actions, during which the pupils will learn the algorithms of educational work, independently learn new knowledge. The main activity of the student - educational, important is the development of intellectual characteristics, ensuring the success of educational activities, social and psychological adaptation and preservation of mental health. Indicator of a favorable functional state of the individual is a proper mental capacity, in the process of which a positive emotional state is achieved. The technologically oriented approach of the process and activity component of the professional training of future engineers is realized through the structure and content of training taking into account the social order, the needs of the labor market, the requirements of the employers of the relevant industry, Ukrainian and international standards. Higher education institutions are focused on the provision of individualized learning, taking into account the maximum satisfaction of mass demand in quality teaching of knowledge